(3eajO GdYHGO ShGA GdYGca ajg hGdHGOs - (3CMeO Hf GdHTjQ GdZdGhj,J (B1277 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO adeG cGf WdH GdYde ef Cge GdegeGJ hCaVd GdWGYGJ hcGfJ efXheI GdTjN GHf YGTQ QeRJ ai cKjQkG ef Ydhe GdOjGfGJ CQOJ Cf GVY YdjgG JbjjOkG jfJaY Hg Ef TGA Gddg JYGdi s
(3BNQgG (B:s
(3Ke bGd HYO cdGeg ai eLGgOg GdfaS eG fUg dcf Pdc HYO GdEaJbGQ Edi SHMGfg hWdH GdYhf ai cd GddMXGJ hEdG adG jfaY GdMPQ hGdLgGO hGdgLQI ai GdZGdH dg s
(3GdfSNI HgG MhGTs
(3GdfSNI YdjgG ebGHdGJ hbQGAGJs
(3HgG BKGQ QWhHI eeG JSHH ai JBcd HYV CWQGagG s
(3eYfhfg HGdMHQ GdCMeQs
(3hJfJgi HNGJeI HYO EfJgGA GdcJGH JbY ef GdUaMI (B325 (3Edi GdUaMI (B340 (3hgj JTJed Ydi KdGK hSJjf aGFOI hYdi cd UaMI HCYdGgG cdeI Gddge Udi Ydi eMeO hYdi s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs